2008
DOI: 10.1042/bj20071392
|View full text |Cite
|
Sign up to set email alerts
|

Association of human DNA helicase RecQ5β with RNA polymerase II and its possible role in transcription

Abstract: Although RecQ5beta is a ssDNA (single-stranded DNA)-stimulated ATPase and an ATP-dependent DNA helicase with strand-annealing activities, its cellular function remains to be explored. In the present paper, we used immunopurification and MS-based analyses to show that human DNA helicase RecQ5beta is associated with at least four RNAP II (RNA polymerase II) subunits. RecQ5beta was also present in complexes immunoprecipitated using three different antibodies against the large subunit of RNAP II, or in complexes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
(33 reference statements)
4
49
1
Order By: Relevance
“…3e and Supplementary Fig. 7), is important for providing resistance to both transcription-and TOP1-induced genome instability [13][14][15]17 . Interestingly, we found that similar to SRSF1 and PIAS1 knockdown, RECQ5 depletion also abolished TOP1 K391/K436 SUMOylation, and this defect is specific to RECQ5 but not other RECQ family DNA helicases, such as BLM (Fig.…”
Section: Top1 Is Sumoylated At K391 and K436 During Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…3e and Supplementary Fig. 7), is important for providing resistance to both transcription-and TOP1-induced genome instability [13][14][15]17 . Interestingly, we found that similar to SRSF1 and PIAS1 knockdown, RECQ5 depletion also abolished TOP1 K391/K436 SUMOylation, and this defect is specific to RECQ5 but not other RECQ family DNA helicases, such as BLM (Fig.…”
Section: Top1 Is Sumoylated At K391 and K436 During Transcriptionmentioning
confidence: 99%
“…Human RECQ5, a member of the highly conserved RECQ family of DNA helicases and a tumour suppressor 12 , is a stable RNA polymerase II (RNAPII)-interacting protein in vivo 13,14 . RECQ5 is important for preventing both transcription-associated DSBs and DSBs induced by TOP1 poisons, such as camptothecin (CPT) [15][16][17] .…”
mentioning
confidence: 99%
“…Pulled-down proteins were separated on a gel by SDS-PAGE; the gel was cut into some pieces, each of which was subjected to in-gel digestion with trypsin [30], and the resulting peptides were analyzed using a nanoflow LC-MS/MS system with qua-drupole-time-of-flight 2 hybrid mass spectrometer (Q-Tof2, Micromass, Wythenshawe, UK) as described [31,32]. The peptide mixture was applied to a Mightysil-RP-18 (3 µm particle, Kanto Chemical, Osaka, Japan) fritless column (45 mm×0.150 mm i.d.)…”
Section: Protein Identification By Lc-ms/msmentioning
confidence: 99%
“…RNA polymerases that are involved in the elongation of RNA transcripts have been considered as helicases that unwind the dsDNA to expose the ssDNA strand that serves as the template for RNA synthesis [2]. Helicases thus play a role in most transcriptional processes including activation (TFIIH), initiation (TFIIH, SNF2), maintenance (SW1), DNA repair (TFIIH, ERCC6/RAD26), and termination (Factor 2, Rho) [49, [66][67][68][69][70][71][72].…”
Section: Functions Of Helicasesmentioning
confidence: 99%